Rare Case of Giant Proliferating Trichilemmal Tumor Behind Left Shoulder: A Case Report - Abdul Ahad Riaz; Faisal Naseer; Allahdad Khan; Muhammad Asjad Sheikh; Linta Malik; Aseel Kamal; Anam Malik (Clinical Case Reports)
ABSTRACT Proliferating trichilemmal tumor (PTT) is a rare, benign adnexal tumor of hair follicles that commonly mimics malignancy. Excellent outcomes can be achieved with early surgical excision. Delayed presentations—as in this giant shoulder PTT—are made possible, in part, by patient education and healthcare accessibility in low‐resource settings.